Reproductive Hormones - Marsh, Courtney (IntechOpen, 2021)
Reproductive Hormones examines the pathophysiology of reproductive hormones on the human body. The breadth of the book's content is extensive, covering the effects of sex steroids on multiple organ systems. New information is presented in a clear, concise fashion and material is clinically relevant to practicing providers in endocrinology and other specialties.